Whole genome sequencing improves the discrimination between Mycobacterium bovis strains on the southern border of Kruger National Park, South Africa - Eduard O. Roos; Johannes Loubser; Tanya J. Kerr; Anzaan Dippenaar; Elizma Streicher; Francisco Olea-Popelka; Suelee Robbe-Austerman; Tod Stuber; Peter Buss; Lin-Mari de Klerk-Lorist; Robin M. Warren; Paul D. van Helden; et al. (One Health, 2023)
Background: Mycobacterium bovis forms part of the Mycobacterium tuberculosis complex and has an extensive host range and zoonotic potential. Various genotyping methods (e.g., spoligotyping) have been used to describe the molecular epidemiology of M. bovis. Advances in whole genome sequencing (WGS) have increased resolution to enable detection of genomic variants to the level of single nucleotide polymorphisms. This is especially relevant to One Health research on tuberculosis which benefits by being able to use WGS to identify epidemiologically linked cases, especially recent transmission. The use of WGS in molecular epidemiology has been extensively used in humans and cattle but is limited in wildlife. This approach appears to overcome the limitations of conventional genotyping methods due to lack of genetic diversity in M. bovis. Methods: This pilot study investigated the spoligotype and WGS of M. bovis isolates (n = 7) from wildlife in Marloth Park (MP) and compared these with WGS data from other South African M. bovis isolates. In addition, the greater resolution of WGS was used to explore the phylogenetic relatedness of M. bovis isolates in neighbouring wildlife populations. Results: The phylogenetic analyses showed the closest relatives to the seven isolates from MP were isolates from wildlife in Kruger National Park (KNP), which shares a border with MP. However, WGS data indicated that the KNP and MP isolates formed two distinct clades, even though they had similar spoligotypes and identical in silico genetic regions of difference profiles. Conclusions: Mycobacterium bovis isolates from MP were hypothesized to be directly linked to KNP wildlife, based on spoligotyping. However, WGS indicated more complex epidemiology. The presence of two distinct clades which were genetically distinct (SNP distance of 19–47) and suggested multiple transmission events. Therefore, WGS provided new insight into the molecular epidemiology of the M. bovis isolates from MP and their relationship to isolates from KNP. This approach will facilitate greater understanding of M. bovis transmission at wildlife-livestock-human interfaces and advances One Health research on tuberculosis, especially across different host species.